Postmodernism: theory and practice of multiculturalism in Europe - Kosherbayev, Zhanbolat; Nurysheva, Gulzhikhan; Mombek, Aliya; Kuzhagulova, Gulnar; Kamalova, Nasipkhanym; Remizov, Viacheslav (Calitatea Vieții, 2016)
The article describes the basic concepts and views on the policy of multiculturalism, using the example of European countries (the United Kingdom, Germany and France). The research is focused on three main objectives: analyzing the concept of multiculturalism in the context of postmodernism, identifying its strengths and weaknesses and giving a detailed analysis of the consequences of multiculturalism in different European countries. The author also discusses the perspectives of the policy of multiculturalism, as well as the cultural and social policy in relation to different cultures in Europe. The research is based on a set of systemic and dialectical methods that consider the research question as a complex emerging phenomenon including a number of interacting and interrelated levels: theoretical, socio-economic, cultural and political. The author assumes that the policy of multiculturalism can contribute to the further democratization of the international community, but a positive result is possible only through a thorough study and analysis of the specific features of each society.